Productivity of ICT and non-ICT capital: The role of rates of return and capital prices - Thomas Niebel; Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We investigate the role rates of return and rates of asset price decline play in explaining sources of productivity growth in the context of a growth accounting approach. Our analysis is based on data from the EU KLEMS database for seven countries in the period of 1990 - 2007. We introduce a constant rate of return to capital and a constant rate of ICT price decline across sectors, countries and time. The main result of this sensitivity analysis is that both alternative measurements somewhat downplay the role investment played relative to growth in multi-factor productivity in the UK and the US during 1995 - 2000. Moreover, we show that more than half of the ICT contribution to labor productivity growth results from growth in capital quality and composition rather than quantity.
Keywords: C43; E22; O33; O47; 330; ICT capital; asset prices; rates of return; growth accounting; Return on Investment; Informationstechnik; Kapital; Capital Asset Pricing Model; Arbeitsproduktivität; EU-Staaten